A Comprehensive Analysis of Population Differences in LRRK2 Variant Distribution in Parkinson's Disease - Shu, Li; Zhang, Yuan; Sun, Qiying; Pan, Hongxu; Tang, Beisha (Frontiers in Aging Neuroscience, 2019)
Background:LRRK2 variants have been demonstrated to have distinct distributions in different populations. However, researchers have thus far chosen to focus on relatively few variants, such as R1628P, G2019S, and G2385R. We therefore investigated the relationship between common LRRK2 variants and PD risk in various populations. Methods: Using a set of strict inclusion criteria, six databases were searched, resulting in the selection of 94 articles covering 49,299 cases and 47,319 controls for final pooled analysis and frequency analysis. Subgroup analysis were done for Africans, European/West Asians, Hispanics, East Asians, and mixed populations. Statistical analysis was carried out using the Mantel-Haenszel approach to determine the relationship between common LRRK2 variants and PD risk, with the significance level set at p < 0.05. Results: In the absence of obvious heterogeneities and publication biases among the included studies, we concluded that A419V, R1441C/G/H, R1628P, G2019S, and G2385R were associated with increased PD risk (p: 0.001, 0.0004, < 0.00001, < 0.00001, and < 0.00001, respectively), while R1398H was associated with decreased risk (p: < 0.00001). In East Asian populations, A419V, R1628P, and G2385R increased risk (p: 0.001, < 0.00001, < 0.00001), while R1398H had the opposite effect (p: 0.0005). G2019S increased PD risk in both European/West Asian and mixed populations (p: < 0.00001, < 0.00001), while R1441C/G/H increased risk in European/West Asian populations only (p: 0.0004). Conclusions: We demonstrated that LRRK2 variant distribution is different among various populations, which should inform decisions regarding the development of future genetic screening strategies.